Evaluación y propuesta de una infraestructura de red inalámbrica que garantice el acceso a los servicios informáticos para el Campus la Dolorosa de la Universidad nacional de Chimborazo. - Valdiviezo Naranjo, Santiago Guillermo (2016)
Assessment and proposal of a wireless network infrastructure that guarantees access to computer services for campus “La Dolorosa” of Universidad Nacional de Chimborazo. In the resources it was possible to have ETSI EG 202 057-4 standard on internet quality access, the application Pingdom website for the measurement of websites, the descriptive and the explanatory method were used, documentary and field research. With the obtained results it was possible to get the achieved objectives, analyzing the state of the art of components of the wireless network infrastructure and TIC in education, it was proved the traffic that flows through the open wireless network thus it is designed infrastructure wireless network. With the help of cisco packet tracer could simulate the optimal wireless network for future implementation. It is concluded that the campus “La Dolorosa” there are approximately 3266 mobile devices which generate a total of 5,598 traffic Gbps high quality and 0.795 Gbps at acceptable quality this includes a fairly high traffic. The use of updated standards is recommended in order to obtain data on bandwidth required.